FROM THE RESULTS OF NEW ARCHAEOLOGICAL SURVEYS CARRIED OUT IN THE SANGANAK (MAKRID) SOY BASIN IN THE KITAB DISTRICT - Normurodov D. R. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the results of new archaeological surveys conducted in the Sanganak (Makrid) stream basin of the Kitab district. During the research, new monuments of Sayyodtepa-1 and Sayyodtepa, dating back to late antiquity and the Middle Ages, and rock paintings were discovered, as well as new ceramic items, millstones, and tombstones from monuments identified in previous studies. The location, periodicity, and functional characteristics of the identified monuments indicate the continuous development of the territory over a long historical period. The article serves to expand the archaeological map of the Sangansansoy basin and reconstruct the stages of historical and cultural development of the region.